2019
DOI: 10.3389/fimmu.2019.02049
|View full text |Cite
|
Sign up to set email alerts
|

TRIM21—From Intracellular Immunity to Therapy

Abstract: Tripartite motif containing-21 (TRIM21) is a cytosolic ubiquitin ligase and antibody receptor that provides a last line of defense against invading viruses. It does so by acting as a sensor that intercepts antibody-coated viruses that have evaded extracellular neutralization and breached the cell membrane. Upon engagement of the Fc of antibodies bound to viruses, TRIM21 triggers a coordinated effector and signaling response that prevents viral replication while at the same time inducing an anti-viral cellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
93
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(93 citation statements)
references
References 127 publications
(217 reference statements)
0
93
0
Order By: Relevance
“…It has been found that in mouse and human systems, HAdv-Ab complexes are recognized in the cytosol by cytosolic protein tripartite motif containing-21 (TRIM21), which binds to the Fc portion of the Ab and targets HAdv-Ab complexes for proteasomal degradation [28,29]. An in-depth review of TRIM21dependent neutralization of HAdv-Ab complexes in the cytosol was recently published elsewhere [32]. It should be noted, however, that the TRIM21-dependent mechanism of intracellular degradation of HAdv-Ab complexes does not operate in all cell types.…”
Section: Humoral Factors Affecting Hadv Bio-distribution After Intravmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been found that in mouse and human systems, HAdv-Ab complexes are recognized in the cytosol by cytosolic protein tripartite motif containing-21 (TRIM21), which binds to the Fc portion of the Ab and targets HAdv-Ab complexes for proteasomal degradation [28,29]. An in-depth review of TRIM21dependent neutralization of HAdv-Ab complexes in the cytosol was recently published elsewhere [32]. It should be noted, however, that the TRIM21-dependent mechanism of intracellular degradation of HAdv-Ab complexes does not operate in all cell types.…”
Section: Humoral Factors Affecting Hadv Bio-distribution After Intravmentioning
confidence: 99%
“…Indeed, HAdv mutants unable to bind to coagulation FX could still transduce hepatocytes with very high efficiency after intravenous administration into complement C1q-or C4-deficient mice [26], which have normal levels of circulating natural IgM that form HAdv-Ab immune complexes after intravenous virus administration. An in-depth review of TRIM21dependent neutralization of HAdv-Ab complexes in the cytosol was recently published elsewhere [32].…”
Section: Humoral Factors Affecting Hadv Bio-distribution After Intravmentioning
confidence: 99%
“…This review focuses on the cell‐based effector functions that arise from the interaction of IgG with the classical human leukocyte FcγR 7. Although beyond the scope of this review, it should be noted that the IgG‐Fc portion dictates other aspects of an antibody’s biology, including its serum half‐life mediated by the neonatal FcR (FcRn), 3 the activation of complement C1,8 antiviral protection via the intracellular receptor TRIM219 and interactions with the Fc receptor‐like family 10…”
Section: Introductionmentioning
confidence: 99%
“…TRIM21 uses antibodies as intermediary molecules to target a wide-range of substrates for proteasomal degradation including viruses (Fan et al, 2016;Mallery et al, 2010;Vaysburd et al, 2013;Watkinson et al, 2015), bacteria (McEwan et al, 2013;Rakebrandt et al, 2014) and proteopathic agents such as Tau (McEwan et al, 2017). TRIM21 underpins a system of intracellular immunity where the diversity of the body's antibody repertoire can be utilized in the cytosol to degrade invading pathogens (Foss et al, 2019;McEwan et al, 2011). This broad-spectrum targeting capability of TRIM21 has recently been exploited to develop Trim-Away, an easy to use and powerful method for acute and rapid degradation of endogenous cellular proteins.…”
Section: Introductionmentioning
confidence: 99%